Volleyball injuries: A survey of injuries among male players of the Chinese Taipei national volleyball team - Huang, H.-Y.; Teng, T.-L.; Liang, C.-C. (American Journal of Sports Science, 2015)
Volleyball is a sport involving rapid and forceful movements of the body as a whole. Because of the large forces involved in such movements, it is inevitable that injuries occur. If injuries are inflicted during a game, they primarily occur in the lower extremities, and particularly in the ankles, knees, and feet, which are used for jumping and landing. Previous studies have recorded only the frequency with which various injuries occurred during matches; the type and severity of injury during training sessions were not explored. In this study, questionnaires were designed to discover the injuries that the players sustained during training for the 2014 Asian Games in Incheon, South Korea. This study aimed to identify and analyze the types and locations of frequent injuries in volleyball players during varying training phases. The results revealed that the percentage of incidences of injuries in the second session was greater than that in the first session in terms of affecting training, whereas the percentage of incidences of injuries in the first session was greater than that in the second session in terms of preventing players from playing in competitions. Furthermore, coaches should be aware of the types and location of injuries that players may sustain during various sessions of training, and accordingly advise players on how to prevent injuries before they occur. The analytical results obtained here have potential for guiding the injury-preventive measures in volleyball.